THE EFFECT OF NON-DENTAL GLASS FIBER COMBINATION ON FLEXURAL STRENGTH OF PREPOLYMERIZED FIBER-REINFORCED COMPOSITE - Muhammad Dian Firdausy; Eko Hadianto; Arina Zuhaila Amna (Jurnal Medali, 2022)
Background: Fiber reinforced composite is a combination of composite resin and fiber. Fiber in FRC serves as a reinforcement to be resistant to fractures. One of the fibers used in FRC is dental glass fiber because it can increase mechanical strength. Dental glass fiber is very limited and expensive while glass fiber which available in the market is non dental glass. This material has mechanical properties almost same as dental e-glass fiber used in dentistry, so it can be used as an alternative material FRC. The aim of this study was to identify the effect of flexural strength of non dental glass fiber to prepolymerized fiber reinforced composites.Method: This study used true experimental design with 16 samples. The samples were divided into two groups according to prepolymerized composite resin groups without fiber and prepolymerized composite resins with the addition of non dental glass fiber. Data analysis in this study used the normality test with the Sapiro-Wilk test, levene test and independent t-test. Result: The results were statistically analyzed, the average flexural strength of prepolymerized composite resin without fiber is 36.60 MPa and prepolymerized composite resin with the addition of non dental glass fiber which is 54.26 MPa. Based on the normality test and the levene test values (p> 0.05) and independent t-test values (p <0.05) were obtained.Conclusion: The conclusion obtained that there is an effect of the addition of non dental glass fiber to the flexural strength of prepolymerized fiber reinforced composite.